Umat Katolik Lingkungan St. Kristoforus dalam Bayang-Bayang Urban Malang: Communio dan Dialog dalam Komunitas Basis Gerejawi - Hermiawan, Nikodemus (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2019)
The focus of this article is the problem of identity of the Catholics in the urban city of Malang. Based on observation and discussion with the Catholics in the St. Christophers’ neighbourhood, St. Vincent de Paul Parish of Langsep, has come up to an idea that people in the city are individualistic. The writer presumes that today globalization of the cities affects the way of thinking of the Catholics. The people practice their religious duties as far as such activities do not disturb their business. On the other hand, the spirit of urban societies is so dynamic in line with the spirit of the times. Every citizen seems to be motivated by the condition to adapt him-/herself within the progress of the age. In this urban rhythm the Catholics in the neigbourhood feel oblige to protect themselves from these influences and then strive to keep themselves away from the noise of the city. As the minority group, they seem to be reluctant to associate with the majority, since it may disturb their comfort. This is practically their challenge, how to open their exclusiveness and build a communio of the faithfuls who go forth and engage in dialogue with people of other faiths dan with the local culture.